Respostas Fisiológicas de Chlorella sorokiniana sob diferentes condições de cultivo e aplicação de sua biomassa - Montanhim, Graziela Cristina (2018)
Microalgae are promising photosynthetic organisms, thus important for the biofixation of the CO2. They have the potential for application in various industrial sectors, such as in the production of renewable energy and in the area of fine chemistry. Microalgae biomass carries valueable biomolecules such as lipids, carbohydrates and proteins that can have their production optimized, depending on culture conditions. Species selection and identification of conditions that stimulate their growth is important for the development of large-scale cultures. The objectives of this research were to investigate the physiology of a Chlorophyta microalgae in different scales, analyse its biochemical composition and apply its biomass. For the development of this research we selected Chlorella sorokiniana among three Chlorophyta species based on growth rate, biomass yield and protein production in laboratory controlled experiments. These results are presented in chapter 1. In chapter 2, we scaled C. sorokiniana cultures up to 100 and 1000 L keeping them outdoors for the production of biomass and physiology evaluation under the natural conditions of light and temperature. The results showed less proteins and lipids in the biomass of large scale systems in comparison to the laboratory cultures. Although the phtosynthetic capacity was similar in either scale, the highest rate of carbon fixation was obtained in 100 L cultures. In chapter 3 the applicability of the biomass produced in the 1000 L cultures was investigated in vegetable seeds pelleting, whose viability was evaluated by monitoring the pelletized seeds germination. These results showed ~ 90% emergence and equivalence with the controls, so confirming the applicability of microalgae biomass in the composition of seed pelleting materials. Finally, in the 4th chapter we investigated if light emiting diodes (LEDs) of different colors would led to improvements in C. sorokiniana growth, biomass and photosynthetic physiology. For this, the cells were exposed to blue, red and a blend of 50% each blue and red LEDs accomplishing 100% of PAR as in the controls (white LED). We observed that S. sorokiniana exposed to red LED had the lowest biomass productivity (0.0025 mol C [mg Chl a-1 h-1]), dry biomass and growth rates and it was the most sensible culture to photosynthetic light reactions. Cultures exposued to the blue, and the blend of blue/red LEDs showed photosynthetic behavior similar to the control, in addition to higher biomass yield. From the present research as a whole we can conclude that C. sorokiniana is a robust freshwater Chlorophyta that supports the adverse conditions of outdoor cultures and that its biomass can be used in seeds pelleting. In addition, we showed that blue LED can improve C. sorokiniana productivity and modify its biochemical composition.